2019
DOI: 10.1128/aem.02129-18
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Oxide Biomineralization Provides Protection against Nitrite Toxicity in a Cell-Density-Dependent Manner

Abstract: We present here a direct fitness benefit (i.e., growth advantage) for manganese oxide biomineralization activity in Roseobacter sp. strain AzwK-3b, a model organism used to study this process. We find that strain AzwK-3b in a laboratory culture experiment is growth inhibited by nitrite in manganese-free cultures, while the inhibition is considerably relieved by manganese supplementation and manganese oxide (MnOX) formation. We show that biogenic MnOX interacts directly with nitrite and possibly with reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…[ (Lowenstam and Weiner 1989;Weiner and Wagner 1998;Dove et al 2003;Aparicio and Ginebra 2016;Ensikat et al 2016;Kattimani et al 2016;Endo et al 2018). Lichtenegger et al (2002) Fayek et al 2005;Hazen et al 2009;Wufuer et al 2017); formation of autunite group uranium phosphates (Liang et al 2015;Beazley et al 2017); oxidation or reduction of iron oxide, sulfide, or sulfates (Pósfai et al 1998;Akai et al 1999;Coker et al 2008;Boyd and Druschel 2013;Berg et al 2014Berg et al , 2020, notably to form internal "magnetosomes" of magnetite or greigite for microbial navigation (Chang and Kirschvink 1989;Lins et al 2007;Pósfai et al 2013;Uebe and Schüler 2016); and manganese redox reactions to form a number of species [e.g., vernadite, todorokite, birnessite, rhodochrosite;Carmichael and Bräuer 2015;Kelm et al 2015;Li et al 2016;Zerfaß et al 2019;Galezowski et al 2020;Lu et al 2021). Some researchers have suggested that seafloor manganese nodules form, at least in part, through such biochemical processes (Lysyuk 2008;Blöthe et al 2015).…”
Section: Stage 10a Neoproterozoic Oxygenation and The Phanerozoic Biosphere The Phanerozoicmentioning
confidence: 99%
“…[ (Lowenstam and Weiner 1989;Weiner and Wagner 1998;Dove et al 2003;Aparicio and Ginebra 2016;Ensikat et al 2016;Kattimani et al 2016;Endo et al 2018). Lichtenegger et al (2002) Fayek et al 2005;Hazen et al 2009;Wufuer et al 2017); formation of autunite group uranium phosphates (Liang et al 2015;Beazley et al 2017); oxidation or reduction of iron oxide, sulfide, or sulfates (Pósfai et al 1998;Akai et al 1999;Coker et al 2008;Boyd and Druschel 2013;Berg et al 2014Berg et al , 2020, notably to form internal "magnetosomes" of magnetite or greigite for microbial navigation (Chang and Kirschvink 1989;Lins et al 2007;Pósfai et al 2013;Uebe and Schüler 2016); and manganese redox reactions to form a number of species [e.g., vernadite, todorokite, birnessite, rhodochrosite;Carmichael and Bräuer 2015;Kelm et al 2015;Li et al 2016;Zerfaß et al 2019;Galezowski et al 2020;Lu et al 2021). Some researchers have suggested that seafloor manganese nodules form, at least in part, through such biochemical processes (Lysyuk 2008;Blöthe et al 2015).…”
Section: Stage 10a Neoproterozoic Oxygenation and The Phanerozoic Biosphere The Phanerozoicmentioning
confidence: 99%
“…They are ubiquitous in nature and are well investigated and described, including possible mechanisms of the biomineral formation, in numerous review papers [ 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Diverse Mn(II)-oxidizing organisms produce nanoorganized structures called Mn(IV) bio-oxides [ 105 ], biogenic manganese oxides (BioMnO x ) [ 109 ], or manganese oxide biominerals [ 110 ] (see Table 1 ); with a broad variety of morphologies such as biomineralized sheaths, globules, lamellas or nanonodules [ 111 ].…”
Section: Biogenic Manganese Oxidesmentioning
confidence: 99%
“…The core aspects of this scenario, i.e. a cell-secreted enzyme mediating a reaction in the bulk is also found in cases outside of substrate uptake, for example in de-toxification of the environment (Zerfass et al, 2019). In ChemChaste, this scenario is readily modelled through implementation of bulk reactions and coupling of cellular metabolic reactions and environmental…”
Section: Coupled Cell-chemical Environment Simulations In Chemchastementioning
confidence: 99%